Evaluating the Dispositions of Teacher Education Candidates: A Place for Self-Assessment - Amneh Al-Rawashdeh; Gary Ivory; Jeanette H. Writer (Journal of Educational and Psychological Studies, 2017)
The study explored how New Mexico State University (NMSU) teacher candidates understand the assessment form, the assessment process, and the meaning of dispositions assessment according to NCATE standards as related to their development of professional dispositions. The study utilized a qualitative methodology. We used the focus group method with four groups: elementary (N=3), secondary (N=10), early childhood (N=6), and special education candidates (N=4). We asked teacher candidates about their understanding of dispositions and the dispositions assessment process at the beginning of their program and at the end of their program. Based on the analysis, we found that self-assessment of dispositions at this institution is well-grounded conceptually, and the teacher education candidates found the process to be meaningful to them, but that teacher education candidates‟ perspectives suggest it has been flawed in execution. We conclude with recommendations both for the teacher education program we have studied and for teacher education accreditation agencies.